30 Months Clinical Evaluation of Posterior Composite Resin Restorations - Akarsu, Serdar; Özdemir Hüseyin Özgür (The Journal of Dentists, 2018)
Background/Purpose: Popularity of tooth-colored restorations increased with the development of restorative materials and dentin adhesives in the last five years. The aim of this study was to evaluate two posterior composite resins (Surefil and FiltekTM P60) for 30 months in vivo. Materials and methods: In this study, 72 Class II restorations were placed in 62 patients. The restorations were evaluated and scored alpha according to USPHS criteria. 30 months later, the restorations were reevaluated by independent experienced examiner. Results: Fisher Chi-Square test was used for the statistical analysis. After 30 months, both of the composite resins were found to be successful. There was no significant difference between two groups for marginal integrity, marginal leakage, abrasion resistance, surface texture, surface staining, post-operative sensitivity and seconder caries. However, Class II restorations of SureFilTM (Caulk / Dentsply, UK) were better than FiltekTM P60 (3M ESPE, USA) for interproximal contact (p<0.05).